MODEL INTERNALISASI NILAI RELIGIUS DAN NASIONALIS DI PONDOK PESANTREN DARUL CHALIDI NW PRINGGASELA - Zahratul Aulia; Lalu Sumardi; Hj Yuliatin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
This research aims to: 1) find out the model of internalization of religious and national analysis values at the Darul Chalidi NW Pringgasela Islamic Boarding Scool; 2) to find out what factors influence the internalization of religious values and natiolism at the Darul Chalidi NW Pringgasela Islamic boarding school. This research uses a qualitative approach with a descriptive method. The data collection techniques used are observtion, interviews and documentation. Data analysis techniques use data reduction, data presentation, drawing conclusions. Data validation techniques use technical triangulation, source triangulation, and time triangulation. The results of the ressearch show that the model of internalizing religious and nationalist values is a reflective model which aims to strengethen and develop character values which will be strengthened through existing learning and then prakticing the values that have been learned in everyday life. Meanwhile, the factors conssiting of students interests, talent and motivation, whilw eksternl factors consist of the surrounding environment, family, scool and teachers